Near –IR High Performance LWP Polarizer Design for Optical Laser Systems (International Journal of Scientific Research in Science and Technology, 2025)
This work constitutes a theoretical design and analysis of an optical polarizer filter exhibiting optimal behavior. The design encompasses long wave pass (LWP) polarizers intended for implementation under non-normal incident of near-infrared (NIR) radiation, it encompasses distinct spectral range which spans wavelengths from 900 to 1200 nm and employs two distinct methodologies: analytical and needle optimization. The design of a dielectric multilayer nano-polarizing filter is predicated on four material groups, which are CTe\SiO2, TiO2\SiO2, Nb2O5\SiO2, and HfO2\SiO2, whereby SiO2 denotes a low refractive index, while the other materials in each group signify a high refractive index. The thin films polarizer is deposited on glass substrate. The study focused on the effect of the refractive index ratio of the coating materials (nH/nL) on the filter design at a 57º incidence angle in the near-infrared (NIR) region of the electromagnetic spectrum. A new polarizing filter design with a limited number of layers, a sharp edge, a wide polarization range, and indistinct ripples in the high transmittance Brewster angle region has been achieved. The needle optimization method provides an efficient synthetic approach for producing polarizing filters with a novel structure that can be used in optical laser systems.
Keywords: Interference polarizer filters; Long-wave-pass; Oblique incidence; characteristic matrix theory; transmittance